Harmless - Van Loon, Julienne (Fremantle Press, 2013)
Full of suspense, Harmless, is the tightly woven story of eight year old Amanda, whose father is in prison, and Rattuwat, a Thai man burying his daughter in a strange land. Abandoning their broken-down car on the way to the prison’s visiting hour, Amanda and Rattuwat venture into the trackless scrub of Australia’s outer suburbs. As the day heats up, the sense of menace intensifies and each of them enters the no-man’s-land between safety and peril.